thN Lng Folk 2go: Investigating Future Premoderns™ - Mulholland, Neil; Hogg, Norman (Book collections on Project MUSE., 2020)
Neomedievalisms are cultural practices that breathe a bouquet of premoderns as permanent rehearsals of coming events. Where medievalists may be prone to police the post-medieval weald for 'inauthentic' medievalisms, neomedievalists embrace the articulation and mobilisation of metahistorical 'anachronisms'. To the medievalist, medievalisms provide powerful indexes that reveal how post-medieval societies have variously imagined 'little middle ages' to suit modern agendas. To the neomedievalist, medievalisms are theory-fictions that facilitate ludic speculation on non-modern futurities. While neomedievalist theories have emerged in a variety of fields since the early 1970s -- notably in cultural studies of medievalisms, international relations and literary theory -- there are few applications that synthesise and put the methodologies of these diverse fields into practice. thN Lng folk 2go applies this extant scholarship as an extradisciplinary practice, dramatising the neomedieval turn in (quasi)objects, persons, work, education, travel, food, ethnicity, media, art, hypereconomics and technology. This speculative journey is ghost authored by a trinity of neomedievalist narrators -- Journeyman, Anchorite and Host -- each relic-ing their own curious neomedieval futurities. Drawing its heterogeneous approaches from studies in medievalisms, international relations, literary theory, actor-network theory, anthropology, hypereconomics, art history, aesthetics, ecology, cultural theory, cultural geography, ambience, speculative realism and future studies -- thN Lng folk 2go is both an investigation of and a benefaction to a murmuration of neomedievalisms.